LINGUISTIC INTERPRETATION OF PLANT NAMES IN FOLK MEDICINE AND THE SYSTEM OF LANGUAGE - Rahmatova Madina Bahronovna (The latest news and research in education, 2025)
This article explores the linguistic nature of plant names (phytonyms) within the context of folk medicine and their functioning in the broader system of language. Plant names embody not only botanical characteristics but also cultural memory, symbolic meanings, and traditional healing practices accumulated over centuries. By examining etymology, semantics, and motivational features of medicinal plant names, the study reveals how linguistic forms reflect people’s perceptions of nature, therapeutic beliefs, and cultural values. The research highlights the role of plant names in shaping linguistic worldview and demonstrates their importance as linguistic units that preserve ethnobotanical knowledge and national identity.